PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MELALUI PEMBELAJARAN BERBASIS MASALAH SISWA SMP - Sutiana Ferica Resilona; Wahyu Hidayat; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is motivated by the results of previous research which shows that students' mathematical problem-solving ability is not as expected. One of the learning to improve the problem-solving ability of mathematics is problem-based learning. The purpose of this study is to determine the improvement of students' mathematical problem-solving skills as a result of problem-based learning. This study is a quasi-experiment that implements two lessons: problem-based learning and conventional learning. Population in this research is a student of the junior high school in Regency of West Bandung. Sampling was done by purposive sampling and obtained two classes as research sample. The research instrument used is the test of mathematical problem-solving ability. Based on the results of the analysis, it can be concluded that the improvement of the problem-solving ability of mathematical students who get problem-based learning is better than the students who get conventional learning.